(untitled) - Hodge, Bob (Malden, MA., 2017)
Social semiotics reveals language's social meaning its structures, processes, conditions and effects in all social contexts, across all media and modes of discourse. This important new book uses social semiotics as a one-stop shop to analyse language and social meaning, enhancing linguistics with a sociological imagination.
Keywords: Tương tác xã hội,Social interaction